Principal Management in Optimizing Social Studies Teacher Teaching at SD Islamiyyah 2 Ternate City - Rusni Mangoda; Mohtar Kamisi; Irwan Djumat (SOSIOEDUKASI, 2025)
This study aims to describe the management of school principals in optimizing the learning of social studies teachers at SD Islamiyyah 2 Ternate City. The focus of this research includes planning, implementation, and evaluation carried out by school principals in improving the quality of social studies learning. The research method used was qualitative descriptive with data collection techniques through interviews, observations, and documentation. The results of the study show that school principals play an active role in developing teacher competency improvement programs, providing learning support facilities, and conducting periodic supervision and evaluation. The managerial strategies implemented include increasing teacher professionalism through training and coaching, strengthening collaboration between teachers, and using innovative learning media. With effective management, the quality of social studies learning processes and outcomes at SD Islamiyyah 2 Ternate City has increased significantly